Pengembangan Math Trail Menggunakan MathCityMap Berbasis Etnomatematika Embung Tambakboyo Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa (Universitas Dr. Soetomo, 2023)
The ability to think critically is very important for students in solving contextual problems they face. However, sometimes students still lack critical thinking skills because in classroom learning, they are only required to solve calculation-based problems without understanding the underlying concepts. The purpose of this research is to develop a Math Trail MCM learning activity to enhance students' critical thinking skills. The research method used is Research and Development, with the ADDIE model as the research framework. The result of this study is a developed math trails activity that has been designed, tested, and revised through peer assessment. It is expected that the Math Trails activity will be beneficial. The average assessment score obtained was 3.55, indicating that the development of the learning activity using MathCityMp is good to be implemented in the teaching process. This trail can be used by educators to improve students' critical thinking skills and explore alternative learning models outside the classroom.